Poplar-A Cash Crop for North Indian Farmers - Chandra, J. P. (Indian Forester, 1986)
Though Poplars were known to us, their commercial cultivation is quite new to us. In localities where Poplars can be cultivated, farmers are not able to decide about tree crop for Farm Forestry, for want of enough information available about Poplars. As such history, cultivation, yield, pests and economics of Poplar cultivation are discussed in detail. It is interestingto to note that Poplars are capable to provide an I R R of 39.22. Adoption of Poplar Cultivation will not only increase income and output of farm land but will also reduce pressure on State Forests as sizeable quantity of fuel and industrial wood will be generated out side forest. Role of M/s. Wimco Limited a safety match company in development of Poplar cultivation in forests as well as farms is also discussed. Till October, 1985, 4200 ha of forest and agricultural land was covered wilh Poplar in Haryana, Punjab and Uttar Pradesh.